2004
DOI: 10.3748/wjg.v10.i13.1948
|View full text |Cite
|
Sign up to set email alerts
|

Miniature ultrasonic probes for diagnosis and treatment of digestive tract diseases

Abstract: AIM:To investigate the clinical value of miniature ultrasonic probes (MUPs) for the diagnosis and treatment of digestive tract diseases. METHODS:Endoscopic ultrasonography (EUS) was performed for patients with its indications with 7.5-20 MHz MUPs and double-cavity electronic endoscope. According to the diagnosis of MUPs, patients who had indications of treatment received endoscopic resection or surgical excision. Postoperative histological results were compared with the preoperative diagnosis of MUPs. A few pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…3,4 The high diagnostic accuracy of EUS observed in this study suggested that EUS is preferable for the diagnosis of esophageal leiomyoma. Spiral CT might find an esophageal wall thickening focally for a lesion > 10 mm, but it is not sensitive enough to show an esophageal lesion Յ 10 mm, nor is it able to indicate the nature, origin, or mucosal surface of a lesion.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…3,4 The high diagnostic accuracy of EUS observed in this study suggested that EUS is preferable for the diagnosis of esophageal leiomyoma. Spiral CT might find an esophageal wall thickening focally for a lesion > 10 mm, but it is not sensitive enough to show an esophageal lesion Յ 10 mm, nor is it able to indicate the nature, origin, or mucosal surface of a lesion.…”
Section: Discussionmentioning
confidence: 77%
“…3,4 Therefore, EUS could be a useful technique for the diagnosis of esophageal submucosal tumors, and decisions related to their treatment. 3,4 Therefore, EUS could be a useful technique for the diagnosis of esophageal submucosal tumors, and decisions related to their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative histopathological results showed that the size, origin and number of lesions of all patients were completely consistent with the diagnoses of EUS; the nature of lesions of 70 patients agreed with preoperative EUS diagnosis. Diagnosis accuracy of EUS was 93.33%, which disclosed that EUS was almost as valuable as pathology for duodenal protruding lesions, especially for inflammatory swelling, polyps, extrinsic compressions, cysts, Brunner's gland adenoma and lipoma (Xu et al, 2004;2006;Rösch et al, 2002). However, lesions with an untypical echoic image tend to be misdiagnosed, for instance, polyps, ectopic pancreas or stromal tumors became unspecific under EUS when they were small.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these patients underwent surgery, and the postoperative diagnoses were confirmed to be the same as preoperative EUS diagnosis. It is suggested that EUS has the incomparable superiority in diagnosing polyps, inflammatory protrusions and extrinsic compressions in the duodenum (Xu et al, 2004) that may be difficult for conventional endoscope to examine. Duodenal minor papilla could be easily misdiagnosed as polyps or others; nevertheless, EUS can give right diagnosis due to its echo characteristics (Fig.1h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation